HUBUNGAN PEMAKAIAN KONTRASEPSI SUNTIK DEPO PROVERA JANGKA PANJANG DENGAN BERAT BADAN IBU DI PUSKESMAS BALOI PERMAI KOTA BATAM TAHUN 2018 - Dino Gagah Prihadianto; Acholder Tahi Perdoman (Universitas Batam, 2019)
Increasing the rate of population growth raises various problems, to control population growth can be overcome by family planning methods or contraception. contraception as prevention of pregnancy that can be temporary or can be permanent, long-term use can cause weight gain. This research is a quantitative type with an analytic observational research design with a cross-sectional approach conducted in December-January 2017. The population of this study is mothers who use Depo Provera injections as many as 11,143 people and 40 samples have been included using the research criteria using the method accidental sampling. Data collected using medical records were analyzed to determine the number of samples using Depo Provera contraception, then distributed based on criteria and by measuring body weight. Data were analyzed univariately and bivariate by computer using the chi-square statistical test. Based on statistical test results, it was found that there was a significant relationship between the use of contraceptive depo Provera contraception and body weight with p-value = 0,000 (p <0.05). The results also showed that based on statistical test results it was found that there was a significant relationship between the use of Depo Provera contraception and body weight with p-value = 0,000 (p <0.05). From the results of the study it can be concluded that there is a significant relationship between the use of long-term Depo Provera injection contraception with maternal weight in Baloi Permai Public Health Center, Batam City in 2018.